Moisture Effect on Polyether and Polyvinylsiloxane Dimensional Accuracy and Detail Reproduction - Mary P. Walker, DDS, PhD;1 Cynthia S. Petrie, DDS, MS;2 (Journal of Prosthodontics, 2005)
This investigation evaluated and compared the dimensional accuracy and surface detail reproduction of two hydrophilic polyvinylsiloxane (PVS) and two polyether (PE) impression materials when used under dry and moist conditions.